Application of AHP (Analytic Hierarchy Process) Method in Selecting 6 GB Ram Class Smartphone - Agus Santoso; Anung Widodo (Westscience Press, 2025)
This research aims to find out the selection of Smartphones on the Samsung, Oppo, Redmi and Realme brands in the best 6 GB RAM class. This study uses the AHP (Analythical Hierarchy Process) method. The sample uses five participants, namely 5 respondents. The model begins by identifying the main criteria, namely Price, Design, Battery Power and Engine Power using the main criteria ranking based on expert opinions to be interpreted in AHP. The second stage in the methodology is to identify sub-criteria by determining the Smartphone brands to be ranked, namely Samsung, Oppo, Redmi and Realme. Primary data was collected by interviewing and observing participants who use 6Gb RAM smartphones for more than a year. The results of the study showed that Realme smartphone got the first rank with a value of 0.283 while Redmi got the second priority with a value of 0.275 and Oppo got the third priority with a value of 0.265 and Samsung got the fourth priority with a value of 0.18, these are the results of this research analysis.